Analysis of Validity and Learner Response to the Development of Pro-Environment Based Teaching Materials on Global Warming Material - Andi Anwar; Muliati Syam; Shelly Efwinda (Universitas Lambung Mangkurat, 2024)
Pro˗environmental attitudes are specific actions a person takes to minimize the negative impacts of human activities on the environment and environmental health. This research aims to determine the validity and response of senior high school students to environment˗based teaching materials. This study is classified as research and development (R&D), and the ADDIE model, which stands for analysis, design, development, implementation, and evaluation, is the paradigm used. Two media validators and two material validators verified the teaching materials. The validation results from material aspects obtained a percentage of 1.6% and media aspects a percentage of 6%, both of which are included in the valid category. Students' response results to teaching materials are in the very practical categories, with a mean percentage of 85%. Based on the results of validity and student responses, it can be concluded that the pro-environment-based teaching materials on global warming developed are valid and can be used in the physics learning process in high schools to increase students' knowledge and character towards the environment.